Discursivizações sobre os animais não-humanos: da objetificação ao sujeito de direito - Ferreira, Realina Maria (2022)
This work aims to investigate how non-human animals are discursivized in/by different discourses in history and to reflect on how such discourses relate to each other as networks of meanings from which, in legal discourse, the laws that deal with the lives of non-human animals are formulated. For the study, I started with reflections on discourse analysis and meaning and approached characteristics of legal discourse that allow me to understand its interpretive dimension and as related to social and discursive changes. Afterwards, I discuss anthropocentrism as the predominant thought in the West and within which discourses such as specisism and culture arise to determine the life and exploratory forms of non-human animals. From this, I discuss the practices of mistreatment of non-human animals and their discursivization as thing and property. In the sequence, still within the anthropocentric framework, I approach discursive manifestations said to be cultural and of tradition and that are based exclusively on the exploitation of non-human animals. Finally, I approach the discourses in favor of life and nonexploitation or consumption of non-human animals, when I turn to discourses such as biocentrism, sentience and veganism. Throughout the chapters, we present analyzes of Brazilian laws on the subject and analyzes of other materials, such as transcripts of videos and a podcast, which were gathered by me as the research took place and which allowed me to understand some of the discursivities at stake. This research contributes to the areas of study on speech and language, society and culture, ethics between humans and non-human animals. Keywords: Non-human animals as subjects of law, discourse analysis, legal discourse, animal rights laws.